2001
DOI: 10.1001/archinte.161.15.1866
|View full text |Cite
|
Sign up to set email alerts
|

Nonsevere Community-Acquired Pneumonia

Abstract: Among low-risk patients with community-acquired pneumonia, there was a certain correlation between severity and cause. In contrast, the existence of a comorbidity did not have a predictive causative value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…According to etiologic categories the profile of patients is similar to the combined information from previous studies of CAP [1-4,8]: infections by atypical agents were characterized by milder episodes, while more severe infections were caused by conventional bacteria. In fact, patients with conventional bacteria have higher hospitalization rate, higher CURB65 scores at admission, more bilateral radiographic involvement and more adverse clinical evolution and outcomes such as severe sepsis, septic shock, ICU admission and longer length of stay.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…According to etiologic categories the profile of patients is similar to the combined information from previous studies of CAP [1-4,8]: infections by atypical agents were characterized by milder episodes, while more severe infections were caused by conventional bacteria. In fact, patients with conventional bacteria have higher hospitalization rate, higher CURB65 scores at admission, more bilateral radiographic involvement and more adverse clinical evolution and outcomes such as severe sepsis, septic shock, ICU admission and longer length of stay.…”
Section: Discussionsupporting
confidence: 63%
“…Some studies have found atypical bacteria to be the predominant microorganism for cases of ambulatory CAP [6] and for patients hospitalized with milder episodes of pneumonia [8]. However, population-based studies [1,9] have showed that S. pneumoniae was also the organism most frequently isolated in outpatients, and for each age group, the etiologic profile could be similar among inpatients and outpatients [9].…”
Section: Introductionmentioning
confidence: 99%
“…The identification rate of the causative pathogens of CAP varied from approximately 30% to 85%, depending on the study design, population included, and examination methods of pathogen identification. S. pneumoniae , M. pneumoniae , C. pneumoniae , and Q fever account for 5.6–85%, 0.7–61.3%, 0.1–11%, and 0.3–24%, respectively [18], [21], [29], [30], [33], [35][37], [61], [62]. However, the prevalence of S. pneumoniae is 6.6%, M. pneumoniae is 9.0%, and C. pneumoniae is 7.8%, but no Q fever was identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Mycoplasma has a predilection for the upper, as well as Gastrointestinal involvement is typical for Mycoplasma, and is much less common with C. pneumoniae pneumonia. In a patient with CAP and otherwise unexplained watery diarrhoea associated with pneumonia, the differential diagnostic possibilities are limited to Legionella and Mycoplasma [4][5][6][7][8][9][10][50][51][52][53][54][55][56][57][58]. In patients with advanced cardiopulmonary disease and in compromised hosts, M. pneumoniae or C. pneumoniae CAP may present as severe CAP [59,60].…”
Section: P N E U M O N I a E A N D C P N E U M O N I A E C A Pmentioning
confidence: 99%